Band 4 - Möller, Horst; Cubar'jan, Aleksandr O. (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
Main topics: "The Second World War in Historical Studies and Remembrance Culture in Germany and Russia" "Russian Emigration in Germany, German Emigration in Russia in the 20th Century" The fourth volume of the Mitteilungen der Deutsch-Russischen Historikerkommission documents the colloquia "The Second World War in Historical Studies and Remembrance Culture in Germany and Russia" (Saratov 2005) and "Russian Emigration in Germany, German Emigration in Russia in the 20th Century" (Munich 2006) as well as lectures at a conference on the German Flying School in Lipeck.